Effect of Statins on Survival Following Stroke in Patients With Cancer - Kim, Ye Sel; Park, Moo-Seok; Lee, Jun-Hwa; Chung, Jong-Won; Lee, Mi Ji; Kim, Chi Kyung; Jung, Jin-Man; Oh, Kyungmi; Bang, Oh Young; Kim, Geong-Moon; Choi, Ji-Mi; Lee, Juneyoung; et al. (Frontiers in Neurology, 2018)
The objective of this study was to investigate the potential benefits of statin therapy initiation in acute stroke in patients with active cancer. This study was conducted in two parts. First, data from patients who presented with stroke and active cancer were obtained from prospectively collected multicenter hospital-based stroke registries. Patients were classified into statin user and non-user groups; the statin group was further divided into low-potency and high-potency statin subgroups. The primary outcome was time to mortality. Second, we obtained data from the Korean National Health Information Service-National Sample Cohort (NHIS-NSC) database for external validation and analyzed the effect of statins on mortality, taking compliance into consideration. For the stroke registry cohort, statin use was independently associated with reduced mortality in a multivariable model (hazard ratio [HR] = 0.675, 95% confidence interval [CI] = 0.457–0.996). There was no interaction between statin use and cancer characteristics, vascular risk factors, or laboratory findings. A dose-dependent relationship between statin use and survival was also demonstrated. Analysis of the NHIS-NSC database found a similar association between statin therapy and reduced mortality (adjusted HR = 0.64, 95% CI = 0.45–0.90) and this effect persisted even after controlling for the adherence of statin use (HR = 0.60, 95% CI = 0.41–0.89). Statin therapy could be associated with reduced mortality in patients with acute stroke and active cancer.